Why engendering PRSPs reduces poverty, and the case of Rwanda - Elaine Zuckerman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
To achieve the poverty reduction goal, HIPC countries need to mainstream gender considerations into their PRSPs (poverty reduction strategy papers). Mounting worldwide evidence that greater gender equality correlates with high economic growth and less poverty means that to succeed, poverty reduction strategies must invest in reducing gender disparities. An analysis of completed PRSPs demonstrates that so far the PRSP engendering track record has been disappointing. This paper discusses why PRSPs must address gender concerns, PRSP engendering track records, strategies and deliberate steps necessary to mainstream gender into PRSPs and Rwanda's attempts to produce a gender-sensitive PRSP. – gender ; gender equality ; poverty ; PRSPs ; empowering women
Keywords: D31; I32; J16; J22; 330; Armutspolitik; Geschlecht; Frauen; Ruanda; Gleichberechtigung